2014
DOI: 10.4172/2168-9857.1000124
|View full text |Cite
|
Sign up to set email alerts
|

Mature and Immature Teratoma: A Review of Pathological Characteristics and Treatment Options

Abstract: Testicular teratoma is a sub-type of Non-Seminomatous Germ Cell Tumour (NSGCT) and often occurs in two distinct age groups. Adult testicular teratomas are often mixed and are malignant. Teratoma can be divided histologically into mature and immature. Pure mature teratoma of the testis is rare. Intratubular Germ Cell Neoplasia (ITGCN) is a common feature associated with teratoma. Teratoma is frequently chemoresistant and clinical management of these tumours includes radical inguinal orchidectomy followed by Ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
2
12
0
8
Order By: Relevance
“…H&E histopathological examination of the tumours showed that they resembled immature teratomas, which typically have abundant neuroepithelial cells [ 47 ] as well as derivatives of other germ layers, such as chondrocytes [ 48 ]. The abundant epithelial structures observed in the tumours are likely to resemble either primitive ectoderm epithelia or neuroepithelia.…”
Section: Discussionmentioning
confidence: 99%
“…H&E histopathological examination of the tumours showed that they resembled immature teratomas, which typically have abundant neuroepithelial cells [ 47 ] as well as derivatives of other germ layers, such as chondrocytes [ 48 ]. The abundant epithelial structures observed in the tumours are likely to resemble either primitive ectoderm epithelia or neuroepithelia.…”
Section: Discussionmentioning
confidence: 99%
“…The standard treatment for all testicular tumors in adults is radical inguinal orchiectomy. In the setting of a pure teratoma with advanced disease and elevation of tumor markers, chemotherapy is the systemic therapy of choice [ 14 ]. Approximately 70% to 80% of patients with metastatic disease will be cured with cisplatin-based chemotherapy combined with surgery to resect residual disease as an integral part of management.…”
Section: Discussionmentioning
confidence: 99%
“…Immature forms contain incompletely differentiated components resembling embryonic and fetal tisues. Immature forms of teratomas are commonly detected in adults (4,5). Testicular dermoid cysts are rare benign lesions that may be classified as a variant of mature teratoma whereas they occur in the testis without atrophy and abnormal spermatogenesis (2,4,5).…”
Section: Pure Testicular Teratomamentioning
confidence: 99%